Contrastive Study Of Modality Between English And Javanese: Studi Kontrastif Modality Antara Bahasa Inggris dan Bahasa Jawa - Nuraini; Putri Syuhada; Ermyna Seri (Boraspati Journal: Journal of Bilingualism, Organization, Research, Articles, Studies in Pedagogy, Anthropology, Theory, and Indigenous Cultures, 2025)
This study investigates the expression of modality—the linguistic means of conveying certainty, obligation, and speaker attitude—in English and Javanese short stories through a contrastive analysis. While modality plays a critical role in both languages, its realization exhibits notable cross-linguistic differences. Drawing on semantic and pragmatic frameworks, particularly the typology of modality proposed by Palmer (1986) and Nguyen Hoa (2004), this study categorizes and examines epistemic, deontic, dynamic, and intentional modalities. The findings reveal that English modal verbs tend to maintain relatively fixed meanings, whereas Javanese modality is characterized by greater contextual flexibility, often influenced by affixation and nuanced cultural cues. These contrasts underscore the linguistic richness of Javanese and highlight the importance of understanding modality in second language acquisition. The study contributes to the fields of language pedagogy, translation, and intercultural communication by emphasizing the need for accurate interpretation of modality across linguistic and cultural boundaries.